1979
DOI: 10.1139/v79-491
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of ascorbic acid and hydroquinone by perhydroxyl radicals. A flash photolysis study

Abstract: The oxidation of ascorbic acid (AH2) and hydroquinone (QH2) by photolytically generated HO2•radicals was studied over a broad range of pH. The rate constants of the following processes were obtained[Formula: see text]and[Formula: see text]depending upon two different possible mechanistic interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…, is directly involved in this catalytic reaction. The partial inhibition, however, suggests that superoxide radical anions are produced during this reaction, and they play a role in ascorbate degradation, probably via the superoxidescavenging reaction by ascorbate (31)(32)(33)(34). Together these results indicate that MG-BSA behaves as an enzyme, which has an ability to catalyze the oxidation of ascorbate in the presence of oxygen to produce superoxide radical anion and semi-dehydroascorbate radical.…”
Section: Resultsmentioning
confidence: 92%
“…, is directly involved in this catalytic reaction. The partial inhibition, however, suggests that superoxide radical anions are produced during this reaction, and they play a role in ascorbate degradation, probably via the superoxidescavenging reaction by ascorbate (31)(32)(33)(34). Together these results indicate that MG-BSA behaves as an enzyme, which has an ability to catalyze the oxidation of ascorbate in the presence of oxygen to produce superoxide radical anion and semi-dehydroascorbate radical.…”
Section: Resultsmentioning
confidence: 92%
“…It has been suggested that the superoxide radical 02 may be an intermediate in this II reaction [25]; however, the absence of 02 in oxygenated neutral or alkaline solutions of H2A [25] implies the oxidation step is a single two electron process. H2A has also been shown to undergo a redox reaction with 02 ~ [64,65]. Since H2A is a fairly strong acid it may be expected that this molecule would induce the disproportionation of 02 to H202 and molecular oxygen.…”
Section: The Autoxidation Of Ascorbic Acidmentioning
confidence: 99%
“…The reducing power of AA also endows it with substantial antioxidant properties. Thus, AA recycles vitamin E back into its antioxidant form (Packer et al, 1979) and quenches active oxygen species, i.e., -OH, 0 2 * and l02, which arise as byproducts of single electron transport reactions (Fessenden and Verman, 1978;Bodaness and Chan, 1979;Nadezhdin and Dunford, 1979).…”
mentioning
confidence: 99%